The semantic orientation of the Qur’anic witness in Mughni al-Labib, between Ibn Hisham and the commentators, Bab al-Ain as a model A contextual grammatical study - Albalawi, Salman Saud Muslim (Journal of Arabic Language Sciences and Literature, 2023)
The research aims to identify Ibn Hisham’s directives for (on, on, on, and upon) the semantic meanings in the Qur’anic evidence that came in Mughni al-Labib, and to compare these directives with the directives of the commentators for the verses themselves, and to explore the semantic meanings of the two groups, what was agreed upon and what was broad in meaning. After knowing the contexts related to the Noble Verse, the research assumes that Ibn Hisham and the commentators agreed on two directives, and their opinions differed on other directives.The research did not exclude any verse mentioned in this section of Al-Mughni, except for the verses that came as clarification and citation, or in support of a specific idea. The number of Qur’anic witnesses reached twenty witnesses, and the research concluded that Ibn Hisham had instructions that were unique from those of the commentators, and some of them agreed, and the researcher used In research, the comparative contextual approach is comparative in its procedural sense, based on the difference in the specialized field within one language, and not between two languages.
Keywords: semantic orientation; Ibn Hisham; the intelligent king